De l’agglomération antique de la Croix de la Pierre à la paroisse de Saint-Martin-de-Claix (Beaulieu, Charbonnier-les-Mines - Puy-de-Dôme) : nouvelles données sur la topographie urbaine durant l’Antiquité et sur l’évolution du territoire à l’époque médiévale - Philippe Bet; Bertrand Dousteyssier; Gabriel Fournier (Revue Archéologique du Centre de la France)
The article aims to publish the data acquired during the last five years on the ancient terrain of la Croix de la Pierre (Beaulieu, Charbonnier-les-Mines – Puy-de-Dôme). The results of several archaeological operations (diagnosis, pedestrian surveys and aerial photography) are presented and analyzed. It is now possible to have a clearer view of this town, recently discovered, and its spatial organization. Thanks to textual data, the history of this ancient terrain - abandoned probably at the end of the Early Roman Empire- can be followed during the Middle Ages: it is characterized by the Christianization of area and profound changes in the spatial organization.